Żary – The City of Georg Philipp Telemann - Ciesielski Rafał (Musicology Today)
The paper discusses Georg Philipp Telemann’s presence in Sorau (now Żary in Poland) in 1704–1708, inspirations from Polish folk music in Telemann’s works, as well as projects undertaken by and in the present-day city of Żary with a view to incorporating and commemorating Telemann’s figure and oeuvre in the city’s contemporary culture.